2002
DOI: 10.1002/1521-4176(200205)53:5<306::aid-maco306>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Raman analysis of materials corrosion: the example of SiC fibers

Abstract: Advanced materials (ceramics, fibers, composites...) exhibit unique high temperature properties but long term durability assessment is mandatory on account of high processing costs. We used Raman micro‐spectroscopy to analyze the corrosion resistance of commercially available SiC fibers versus Na+ ions, with or without fiber thermal treatment (in air or in a reducing atmosphere) prior to sodium attack. The lateral resolution of the technique approaches the submicron scale and the analysis of colored materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The detailed Raman spectrum parameters in Tables S1 and S2 were almost identical in the surface and the center, especially identical I A / I G and I D′ / I G values, which indicated that structural differences between the surface and the core of high‐performance carbon fibers were not obvious. Other high‐performance fibers also showed the same trend; for example, according to a series of study by Colomban et al, there was no structure difference on the microscale from the surface to the core of the SiC fibers after the consolidation at high temperatures …”
Section: Resultsmentioning
confidence: 73%
“…The detailed Raman spectrum parameters in Tables S1 and S2 were almost identical in the surface and the center, especially identical I A / I G and I D′ / I G values, which indicated that structural differences between the surface and the core of high‐performance carbon fibers were not obvious. Other high‐performance fibers also showed the same trend; for example, according to a series of study by Colomban et al, there was no structure difference on the microscale from the surface to the core of the SiC fibers after the consolidation at high temperatures …”
Section: Resultsmentioning
confidence: 73%
“…SiC is known to have numerous stable stoichiometric solid crystalline phases, so-called polytypes, the cubic (3C-SiC) and the hexagonal (6H-SiC) being the most common ones [12]. Raman peak parameters such as intensity, bandwidth and wavenumber provide useful information related to the phase distribution and chemical bonding of SiC and SiC fibers [13]. Table 2 gathers the characteristic Raman peak wavenumber for 3C-and 6H-SiC polytypes.…”
Section: Transmission (Tem) and Environmental Scanning Electron Micromentioning
confidence: 99%
“…Peaks located between the 700 cm À1 and 1000 cm À1 are related to the cubic SiC polytype. Satellite peaks around 766 cm À1 are attributed to disordered SiC consisting of a combination of simple polytype domains and nearly periodically distributed stacking faults [13,14]. This explanation is consistent with the high SF density observed in Figure 2.…”
Section: Transmission (Tem) and Environmental Scanning Electron Micromentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, increasing the excitation energy allows probing a smaller penetration depth of the carbon matter. [13,17] As mentioned above, an additional band was required to nicely fit the Raman spectra recorded with 2.41 eV excitation energy. For reproducible quantitative result and because of the dispersive behavior of the D band in wavenumber, a highly intrinsic degree of ordering was used in order to fit the Raman spectra with only the main features D, D and G. Indeed, the polishing process produces an inhomogeneity in the I D /I G ratio.…”
Section: Effect Of the Polishing Process On The Spectral Parametersmentioning
confidence: 99%